2021
DOI: 10.1177/20416695211016483
|View full text |Cite
|
Sign up to set email alerts
|

Verbally Induced Olfactory Illusions Are Not Caused by Visual Processing: Evidence From Early and Late Blindness

Abstract: Olfactory perception is malleable and easily modulated by top-down processes such as those induced by visual and verbal information. A classic example of this is olfactory illusions where the perceived pleasantness of an odor is manipulated by the valence of a verbal label that is either visually or auditorily presented together with the odor. The mechanism behind this illusion is still unknown, and it is not clear if it is driven only by verbal information or if there is an interaction between language functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A prominent research theme across the reviewed articles was the study of hedonics; ten studies considered the impact of odour valence on olfactory processing. Seven of these articles directly contrasted odour valence: two behavioural ( Hudry et al, 2014 ; Kärnekull et al, 2021 ) and five neuroimaging ( Royet et al, 2003 ; Bensafi et al, 2007 ; Callara et al, 2021 ; Gorodisky et al, 2021 ; Torske et al, 2022 ). A further three papers involved discussion of the impact of odour hedonicity on olfactory processes, but did not directly manipulate odour pleasantness ( Bensafi and Rouby, 2007 ; Plailly et al, 2007 ; Morrot et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…A prominent research theme across the reviewed articles was the study of hedonics; ten studies considered the impact of odour valence on olfactory processing. Seven of these articles directly contrasted odour valence: two behavioural ( Hudry et al, 2014 ; Kärnekull et al, 2021 ) and five neuroimaging ( Royet et al, 2003 ; Bensafi et al, 2007 ; Callara et al, 2021 ; Gorodisky et al, 2021 ; Torske et al, 2022 ). A further three papers involved discussion of the impact of odour hedonicity on olfactory processes, but did not directly manipulate odour pleasantness ( Bensafi and Rouby, 2007 ; Plailly et al, 2007 ; Morrot et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Especially for humans, the semantic contexts formed by the language used are important because humans can experience the world based on their language, unlike other animals. Previous studies have shown that different labels presented with identical odors affect the perceived odor quality (Bae et al, 2019), pleasantness (Ayabe-Kanamura et al, 1997;Cornell Kärnekull et al, 2021;de Araujo et al, 2005;Djordjevic et al, 2008;Lundström et al, 2006;Manescu et al, 2014), intensity (Cornell Kärnekull et al, 2021;Djordjevic et al, 2008;Manescu et al, 2014), edibility (Manescu et al, 2014), arousal (Djordjevic et al, 2008), and familiarity (Cornell Kärnekull et al, 2021). Human neuroimaging studies have shown that activities in the secondary and/or downstream olfactory areas, such as the anterior cingulate, hippocampus, and medial orbitofrontal cortex, differ when identical odorants are presented with different labels (Bensafi et al, 2014;de Araujo et al, 2005;Gottfried & Dolan, 2003).…”
Section: Introductionmentioning
confidence: 99%